El arte como medio de transformación - Alméciga, Vanessa; Cubillos, Johana; Moreno, Tania; Monsalve, Juan; Puentes, Katherine; Rodríguez, Alejandra; Torres, Camilo; Jiménez Pulido, Hilba Milena (Lee La LEE, 2023)
El arte como medio de transformación